2015
DOI: 10.1039/c5an00342c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the structure and formation mechanism of amyloid fibrils by Raman spectroscopy: a review

Abstract: Amyloid fibrils are β-sheet rich protein aggregates that are strongly associated with various neurodegenerative diseases. Raman spectroscopy has been broadly utilized to investigate protein aggregation and amyloid fibril formation and has been shown to be capable of revealing changes in secondary and tertiary structures at all stages of fibrillation. When coupled with atomic force (AFM) and scanning electron (SEM) microscopies, Raman spectroscopy becomes a powerful spectroscopic approach that can investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
210
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(219 citation statements)
references
References 108 publications
9
210
0
Order By: Relevance
“…Unique bands were not observed, only varying intensities, with the exception of the calcite bands at the leading edge (region II) 31. The position of the Amide I bands in regions I–IV (1667 cm) corresponds to β‐sheets,32 and agrees with previous in situ infrared spectroscopy of the adhesive interface 33. Tables show vibrational band assignments,34 and intensity ratios ( N = 3; mean ± 95% confidence interval).…”
supporting
confidence: 86%
“…Unique bands were not observed, only varying intensities, with the exception of the calcite bands at the leading edge (region II) 31. The position of the Amide I bands in regions I–IV (1667 cm) corresponds to β‐sheets,32 and agrees with previous in situ infrared spectroscopy of the adhesive interface 33. Tables show vibrational band assignments,34 and intensity ratios ( N = 3; mean ± 95% confidence interval).…”
supporting
confidence: 86%
“…Deep UV resonance Raman spectroscopy (DUVRR) is a powerful tool for structural characterization of aggregated proteins and peptides [29]. The sensitivity of the amide M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 chromophore Raman signature to Ψ dihedral angle makes this technique uniquely capable of differentiating between globular and fibrillar β-sheet conformations and between parallel and antiparallel β-sheets [19,30].…”
Section: Formation Of Acrylodan-labeledmentioning
confidence: 99%
“…This so-called polymorphism can be investigated by scanning electron microscopy (SEM) or atomic force microscopy (AFM)61011. Another common feature of amyloid fibrils is a highly organized hydrogen bonded β-sheet structure core, which is detectable in the bulk sample with various techniques, including solid-state nuclear magnetic resonance (NMR)2, X-ray diffraction2, vibrational circular dichroism12, infrared spectroscopy13, and Raman spectroscopy1415. Single-particle studies on the nanoscale with tip-enhanced Raman scattering (TERS) on insulin fibrils161718 and human islet amyloid precursor peptide (hIAPP) fibrils19 revealed that the surface is not only composed of β-sheet structures but also has a high propensity for α-helix/unordered structures.…”
mentioning
confidence: 99%